VD_FINDINFO ML / 2011 / 236 vom 31. Oktober 2011 - VD Tribunal cantonal (2011)
MEILLEURE FORTUNE, EXCEPTIONMOYEN DE DÉFENSE, ACTION EN CONSTATATION, MOYEN DE DROIT | 265a al. 1 LP, 265a al. 4 LP, 63 CPC (CH)